Up-frameshift Protein 1 Promotes Tumor Progression by Regulating Apoptosis and Epithelial–Mesenchymal Transition of Colorectal Cancer. (December 2021) - Chen, Binlie; Wang, Huaiming; Li, Danfeng; Lin, Xiaosheng; Ma, Zhiyan; Zeng, Yongming
Background : Recently, accumulating evidence confirmed that up-frameshift protein 1 (UPF1) was aberrantly expressed in various cancers. However, the molecular mechanism mediated by UPF1 underlying colorectal carcinogenesis remains unclear.Method : Immunohistochemistry (IHC) and quantitative real-time polymerase chain reaction analysis were used to determine the expression level of UPF1 in colorectal cancer (CRC) tissues. CCK-8, EdU, transwell assay, and flow cytometry were performed to investigate the biological significance of UPF1. Epithelial–mesenchymal transition (EMT) and apoptosis associated markers were detected by western blotting.Results : We found that UPF1 expression was upregulated in CRC tissues and cell lines. Clinical analysis revealed that high UPF1 expression was positively correlated with advanced stage, lymph node metastasis and shorter survival. Knockdown of UPF1 suppressed cell proliferation and cell cycle progression. Functionally, UPF1 promotes tumor metastasis by inducing epithelial to mesenchymal transition. Further investigations revealed that knockdown of UPF1 promoted apoptosis through triggering DNA damage.Conclusions : Taken together, this research revealed that UPF1 plays an oncogenic role in CRC via regulating EMT and apoptosis and may be a potential therapeutic target for CRC.